HDAC Inhibition Modulates Cardiac PPARs and Fatty Acid Metabolism in Diabetic Cardiomyopathy. (30th June 2016) - Lee, Ting-I; Kao, Yu-Hsun; Tsai, Wen-Chin; Chung, Cheng-Chih; Chen, Yao-Chang; Chen, Yi-Jen
Abstract : Peroxisome proliferator-activated receptors (PPARs) regulate cardiac glucose and lipid homeostasis. Histone deacetylase (HDAC) inhibitor has anti-inflammatory effects which may play a key role in modulating PPARs and fatty acid metabolism. The aim of this study was to investigate whether HDAC inhibitor, MPT0E014, can modulate myocardial PPARs, inflammation, and fatty acid metabolism in diabetes mellitus (DM) cardiomyopathy. Electrocardiography, echocardiography, and western blotting were used to evaluate the electrophysiological activity, cardiac structure, fatty acid metabolism, inflammation, and PPAR isoform expressions in the control and streptozotocin-nicotinamide-induced DM rats with or without MPT0E014. Compared to control, DM and MPT0E014-treated DM rats had elevated blood glucose levels and lower body weights. However, MPT0E014-treated DM and control rats had smaller left ventricular end-diastolic diameter and shorter QT interval than DM rats. The control and MPT0E014-treated DM rats had greater cardiac PPAR- α and PPAR- δ protein expressions, but less cardiac PPAR- γ than DM rats. Moreover, control and MPT0E014-treated DM rats had lower concentrations of 5′ adenosine monophosphate-activated protein kinase 2 α, PPAR- γ coactivator 1 α, phosphorylated acetyl CoA carboxylase, cluster of differentiation 36, diacylglycerol acyltransferase 1 (DGAT1), DGAT2, tumor necrosis factor- α, and interleukin-6 protein than DM rats. HDAC inhibition significantly attenuated DM cardiomyopathy through modulation of cardiac PPARS, fatty acid metabolism, and proinflammatory cytokines.